Healthy Weight and Cardiovascular Health Promotion Interventions for Adolescent and Young Adult Males of Color: A Systematic Review. Issue 5 (September 2018) - Garbers, Samantha; Hunersen, Kara; Nechitilo, Meredith; Fisch, Marylynn; Bell, David L.; Byrne, Mary Woods; Gold, Melanie A.
Cardiovascular disease is the leading cause of mortality in the United States, accounting for one fourth of deaths. Higher rates of obesity put Hispanic and Black men at increased risk. The American Heart Association cites diet quality, physical activity, and body weight as alterations responsive to health promotion intervention. Prevention strategies need to begin in adolescence and the emerging adulthood years to impact cumulative risk factors. A scoping review identified search terms and this was followed by a systematic review of Cumulative Index to Nursing and Allied Health Literature (CINAHL) and PubMed databases for articles published in English from January 1, 2002, through May 11, 2017. This review explores community-based content, delivery, recruitment, or retention strategies used with young men of color aged 15 to 24 years. Of 17 articles describing 16 individual interventions and 1 describing multiple interventions (with samples ranging from 37 to 4, 800), 13 reported significant results in one or more domains. No studies specifically targeted the needs of young men and only three had more than 50% male participants. There was a gap in studies that addressed young men in the ages of interest with most interventions reaching participants aged 11 to 19 years. Cultural tailoring was addressed through recruitment setting, interventionist characteristics, community involvement, and theoretical frameworks such as motivational interviewing that allow individual goal setting. Because young men seek access to preventive health services less than young women, it is suggested that interventions that are community based or use push technology (send information directly to the user) be increased.